Dietary baking soda (NaHCO3) therapy recovered urolithiasis-induced kidney injury in mice by inhibition of oxidative stress, pyroptosis, and inflammation through gut-kidney axis - Shuai Liu; Yuchen Gao; Jun Luo; Yanhua Chen; Heng Cao; Zhuifeng Guo; Hongmin Zhou; Zhongwen Hong; Bowen Chen; Xiao Xu; Jingcheng Zhang; Nengliang Duan; et al. (Renal Failure)
Background Urolithiasis is one of the most common urological diseases, and its incidence has increased globally in recent years. Multiple potential mechanisms are involved in urolithiasis, including renal oxidative stress, inflammatory response, fibrosis, pyroptosis, and gut microbiota disturbance. Sodium bicarbonate (NaHCO3) is commonly used clinically to alkalize urine and slow the progression of chronic kidney disease, including urolithiasis. However, the specific mechanism of NaHCO3 in the treatment of urolithiasis is unclear.Methods In this study, we constructed a mice urolithiasis model via intraperitoneal injection of glyoxylate (50 mg/kg) for one week in C57BL/6 mice. Meanwhile, 5% NaHCO3 was added to drinking water in the treatment group. Biochemical detection, immunohistochemical staining, RT-qPCR, and Western blotting were used to assess kidney function and levels of inflammation and pyroptosis. The alteration of gut microbiota in mice treated with NaHCO3 was measured using 16S rDNA sequencing.Results The results demonstrated that NaHCO3 effectively reduced the deposition of CaOx crystal, as well as restored kidney function in urolithiasis-induced kidney injury mice. Moreover, NaHCO3 alleviated oxidative stress and inflammatory response and ameliorated pyroptosis by modulating the NLRP3 inflammasome pathway in kidney. Additionally, it enhanced the intestinal barrier function by up-regulating the expression of tight junction proteins (ZO-1, occludin, and claudin 5), remodeling the gut microbiota, and reducing intestinal inflammation.Conclusion In summary, NaHCO3 exerted a protective effect via the gut-kidney axis in the urolithiasis mice model, suggesting its potential use as a dietary supplementation to be added to daily drinking water for the management of urolithiasis.